INFLUENCE OF PRICE AND PRODUCT QUALITY TOWARDS SALES VOLUME OF PT OTANI - Simanjuntak, Free Antonius; Putra, Aidil (Journal of Financial Management & Accounting, 2024)
Product quality is one of the factors that influences increasing sales volume. Product quality is an important factor in realizing a company's sales goals. With good product quality, it is hoped that consumers will be interested in trying it and will then make the decision to buy the product so that there will be an increase in sales. This research aims to: (1) Know and analyze the effect of price on product sales volume at PT. Otani Medan; (2) Knowing and analyzing the effect of product quality on product sales volume at PT. Otani Medan; (3) Knowing and analyzing the effect of product price and quality on product sales volume at PT. Otani Medan. The number of samples used was 84 people. Data collection techniques through library research and field research. The data sources used are primary data sources and secondary data sources. The data tests carried out are validity and reliability tests, classic assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, and autocorrelation tests. Data analysis techniques used include: multiple linear regression analysis, t-test, F test, and coefficient of determination (R2). From the results of the research that has been carried out, it is known that price has a positive and significant effect on the sales volume of PT products. Otani Medan. Product quality has a positive and significant effect on the sales volume of PT products. Otani Medan. Price and product quality simultaneously have a positive and significant effect on the sales volume of PT products. Otani Medan. Sales volume can be explained by price and product quality variables amounting to 57.4%, while the remaining 42.6% is explained by other variables not examined in this research. The variable that has the greatest influence on sales volume is: price.